พฤติกรรมของสตรีในอำเภอเมืองเชียงใหม่ในการใช้ถุงผ้าเพื่อสิ่งแวดล้อม - ปาริฉัตร ชมภูรัตน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This study aimed to explore behavior of women in Mueang Chiang Mai district in using environmental-friendly fabric bags. Samples were specified to 200 female fabric bag users. Questionnaires were used as the tool to collect data. Then, the data obtained were analyzed by the descriptive statistics, consisting of frequency, percentage and mean. The findings presented that most respondents were 20-29 years old with Bachelor’s degree, worked as private company officer and earned monthly income (regular and extra incomes) at less than 15,000 Baht. The results of the study on behavior of women in Mueang Chiang Mai district in using environmental-friendly fabric bags suggested that advantages of the environmental-friendly fabric bags that the respondents paid the highest level concern on were the ease of use which was portable and usable in any occasions and the reduction of global warming since it was durable and reusable many more times than the plastic bags. The environmental-friendly fabric bags that they mostly used were giveaway product. Type of fabric bags that they usually used was the document/book bag (medium size). They used it for carrying documents/files. Person influencing their decision in using the environmental-friendly fabric bag was referred to the respondents themselves. Frequency in using the fabric bag was found in daily use. They currently owned 2 fabric bags. Most of them bought the fabric bag by themselves at longer than a month ago. The frequency in buying the environmental-friendly fabric bag was at once in 6 months. In each purchasing time, they spent less than or equal to 100 Baht for a bag. Place where they bought the environmental-friendly fabric bag was at the Walking Street. Source of information where they learned about the fabric bag’s shops was from their exploration. The results of the study on marking mix factors presented that the following factors affected the use of environmental-friendly fabric bags among the respondents at high level: price, product, place and promotion, in orderly. Hereafter were shown top 10 sub-factors affecting the use of environmental-friendly fabric bags: 1) being more practicable than plastic bags, 2) being appropriate size to use and reasonable price to quality, 3) having wide-range of prices, 4) being durable, 5) product safety, 6) having alternative sizes, 7) having various designs and patterns, 8) cheap price, 9) having clear price-tag, and 10) product beauty. Based upon the sustainable consumption concept, the findings suggested that most respondents agreed with the socio-economic behavior that companies should promote the use of alternative energies in the community and it should have product innovation and employment in the community. In environmental aspect, they agreed with environmental concerned projects such as water and energy conservation, recycle, and pollution reduction. In personnel and environment aspect, they agreed with the statement saying that human were destroying the restricted environment and themselves, thus they should lessen this behavior by using environmental-friendly products and package.